Vận dụng tư tưởng Hồ Chí Minh về độc lập dân tộc trong bảo vệ chủ quyền biển đảo ở Việt Nam hiện nay - Hoàng, Thị Ngọc Minh (Tạp chí Giáo dục, 2025)
Ho Chi Minh’s thought on national independence holds profound significance as a guiding compass for the development of the cause of safeguarding national independence, sovereignty, and territorial integrity. In the face of increasingly complex developments in the East Sea (South China Sea), hostile forces, reactionary elements, and political opportunists constantly seek to distort, incite, and undermine Vietnam’s sovereignty over its seas and islands. Identifying and proactively countering these activities is of critical importance in the mission of defending Vietnam’s maritime and island sovereignty in the current context. This study analyzes the core content of Ho Chi Minh’s thought on national independence, thereby assessing its application in the protection of Vietnam’s maritime and island sovereignty today, and proposes solutions to enhance the defense of national sovereignty over seas and islands in the coming years. Applying Ho Chi Minh's thought is not only a theoretical and political requirement, but also the basis for building a strong stance and spirit, guiding practical actions in protecting the sovereignty of the sea and islands of the Fatherland.